PENATALAKSANAAN FISIOTERAPI PADA LANSIA DENGAN KASUS FROZEN SHOULDER DI DUSUN LOWOKSARI DESA NGENEP KECAMATAN KARANGPLOSO - Dheya Pratnya Kusuma; Nanik Zainiyah; Atika Yulianti (JURNAL PENGABDIAN MANDIRI, 2025)
Has a Community Health Center which plays an important role in public health. Patient visits at the physiotherapy polyclinic in Lowoksari Hamlet, Ngenep Village for shoulder pain cases from 2023 were 25 patients, while in 2024 it increased by 50 patients. The most common case is shoulder pain with the third highest number of cases. Characterized by complaints of pain in the shoulder which hinders daily activities. Objective: This program was carried out to provide education and demonstrate exercises in cases of shoulder pain in order to reduce and prevent complaints. Method: What was used was education in the form of counseling and distributing posters to the elderly in Lowoksari hamlet, Ngenep village, Malang city. Conclusion: What was obtained from measuring the increase in understanding using pre-test and post-test questionnaires was that there was a significant increase in understanding regarding training with an average pre-test score of 10 and an average post-test score of 85.5